ANALISIS TEKNIK PENGERITINGAN RAMBUT POLA BATU BATA TERHADAP HASIL KERITING DITINJAU DARI STUDI LITERATUR - Zalwa Faldiza Ramadhani; Syahrani Putri Alya; Agnes Serepia Samosir; Laura Evelyn Felicia; Asrah Rezki Fauzani; Mutia Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Hair curling is a hair styling technique that aims to transform hair into curly or wavy curls. The technique used in the curling process influences the final result, including shape, volume, and neatness. One technique used in curling designs is the brick pattern, which involves alternating curling irons. This study aims to analyze the brick pattern hair curling technique and its effect on curling results. The method used in this study was a qualitative method with a literature study approach, reviewing various sources, including books and scientific journals relevant to the research topic. The results indicate that the brick pattern technique produces more natural, less stiff curls, and has a more even volume distribution. This technique can also reduce the parting lines that typically appear with parallel styling techniques. However, applying this technique requires precision and skill to ensure neat and balanced results. Based on the results of the study, it can be concluded that the brick pattern curling technique has the advantage of producing more natural and balanced curl designs. Therefore, this technique can be an option for curling hair, especially for a more natural look.